2018
DOI: 10.1590/s0100-83582018360100108
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress in the Production and Quality of Bidens pilosa and Raphanus raphanistrum Seeds

Abstract: Plants in soils with low water availability may present a reduction of their leaf area and photosynthetic rate, as well as lower assimilated compound supply for seeds. Knowing the physiological quality and seed production of weeds generated under water deficit conditions can help understanding the survival and competition strategies of species. The objective of this work was to evaluate the effect of water stress on the production and germination of Bidens pilosa and Raphanus raphanistrum seeds. Plants were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…[ 38 , 53 ] and B . pilosa [ 54 , 55 ] have some level of drought tolerance and showed a significant difference in the species behavior in response to drought stress. Also, the resilience of both species differed depending on what plant characteristics were considered, although with some variations (especially for Amaranthus sp .)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 38 , 53 ] and B . pilosa [ 54 , 55 ] have some level of drought tolerance and showed a significant difference in the species behavior in response to drought stress. Also, the resilience of both species differed depending on what plant characteristics were considered, although with some variations (especially for Amaranthus sp .)…”
Section: Discussionmentioning
confidence: 99%
“…under similar environmental conditions, echoing Pereira et al . [ 54 ] who showed B . pilosa to be better adapted to drought conditions than Raphanus raphanistrum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity dimension (D 0 ) describes a global view of the system (Leiva et al, 2019;Siqueira et al, 2022), allowing us to verify how the scales are filled by the measurement values. Variations in D 0 values for R. raphanistrum, Commelina ssp., and OW on the sampling dates showed that the scales were filled with measurement values, indicating that the difference in D 0 values for the species under study reflects their ecology (Booth et al, 2003;Brighenti, Oliveira, 2011), mainly with regard to the aggregated distribution (Cheam, Code, 1995;Schaffrath et al, 2007;Chiba et al, 2010;Siqueira et al, 2016;Pereira et al, 2018;Izquierdo et al, 2020;Sousa et al, 2020;Jurado-Expósito et al, 2021). The D 1 dimension is related to the entropy information and quantifies the degree of disorder in the system.…”
Section: Discussionmentioning
confidence: 99%
“…(L.) in summer crops is a response to characteristics of species ecology. According to Lorenzi (2014) and Pereira et al (2018), the species R. raphanistrum (L.) has a high capacity for the production of viable seeds and is a common spontaneous plant for winter crops. Cheam and Code (1995) report that the occurrence of R. raphanistrum (L.), even if at low populational densities, can compromise the productivity of winter crops.…”
Section: Ecology and Weed Managementmentioning
confidence: 99%